The idea of policy design: Intention, process, outcome, meaning and validity. (October 2018) - Colebatch, HK
While policy design is a relatively recent term in the social science literature, the concept itself is ancient. The modernist incarnation, from the mid-20th century onwards, is grounded in the applied social sciences: the systematic calculation of problems, values, practices and outcomes. But in many ways, the confidence of the faith in systematic design was not borne out by experience. It became clear that rather than finding expert designers advising authoritative decision-makers and perhaps monitoring the activities of subordinate 'implementers', the world of policy was populated by multiple participants in distinct organisational locations, with divergent framings, continuing negotiation on practice, and ambiguity in the understanding of outcomes. There is clearly a tension between the image of policy design and the experience of the activity. The response to this tension in the literature on policy design has largely been aimed at reconciling the experience of practice with the norms of instrumental rationality. It has tended to give little attention to the interpretive significance of 'design talk' in the process of governing. This paper argues that 'policy design' is an exercise in giving meaning – framing activity in a way that makes practices and outcomes appropriate and valid – and develops a more comprehensive analysis of 'policy design' as a concept in use in both policy practice and the analysis of that practice.